2018
DOI: 10.2340/16501977-2374
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with work ability following exercise interventions for people with chronic whiplash-associated disorders: Secondary analysis of a randomized controlled trial

Abstract: This study found that neck-specific exercise with a behavioural approach intervention was better at improving self-reported work ability than neck-specific exercise or prescribed physical activity. Improvement in work ability is associated with a variety of factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Our findings related to the efficacy of CBA interventions are consistent with both systematic reviews (Monticone et al, ; Shearer et al, ). They are also consistent with seven of the eight aforementioned randomized clinical trials specifically addressing GA/GEX on function and/or pain in patients with CNSNP (Lo et al, ; Ludvigsson et al, ; Monticone et al, ; Overmeer et al, ; Pool et al, ; Thompson et al, ; Vonk et al, ). These studies collectively concluded that augmenting interventions with GA/GEX did not have a meaningful impact on patient outcomes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Our findings related to the efficacy of CBA interventions are consistent with both systematic reviews (Monticone et al, ; Shearer et al, ). They are also consistent with seven of the eight aforementioned randomized clinical trials specifically addressing GA/GEX on function and/or pain in patients with CNSNP (Lo et al, ; Ludvigsson et al, ; Monticone et al, ; Overmeer et al, ; Pool et al, ; Thompson et al, ; Vonk et al, ). These studies collectively concluded that augmenting interventions with GA/GEX did not have a meaningful impact on patient outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…When considering GA, one study (Vonk et al, ) concluded that there was no difference between intervention groups, whereas a second study (Pool et al, ) reported outcomes in favour of the GA group that were statistically significant but not clinically relevant. In a third study (Lo et al, ), the authors stated that the group receiving GA demonstrated a statistically significant improvement in functional outcomes, although the investigators in this latter study did not address clinical relevance. Similarly, two studies (Monticone et al, ; Overmeer et al, ) reported statistically significant (Monticone et al, ; Overmeer et al, ) and clinically relevant (Monticone et al, ) outcomes in which GEX was more effective in relation to change in function, whereas three studies (Ludvigsson et al, ; Monticone et al, ; Thompson et al, ) found no effect.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Poor work ability is related to the personal factors higher age, neck pain, multiple pain locations, cognitive dysfunction, low health-related quality of life, and pessimistic illness perceptions [7][8][9][10] as well as work-related stress and work dissatisfaction [7]. Associations have been found between pain relief, functional improvement and improvement in work capacity [11]; however, there are few studies evaluating the effect of rehabilitation on work ability or work capacity for individuals with chronic WAD, and thus far the effect is inconclusive [12][13][14]. Adams et al reported only marginal improvement in work ability despite rehabilitation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Adams et al reported only marginal improvement in work ability despite rehabilitation [12]. Work ability was, however, improved after a multi-professional rehabilitation programme with cognitive behavioural therapy [13] and after neck-speci c exercises with and without a behavioural approach [14].…”
Section: Introductionmentioning
confidence: 99%